Construction of solid–liquid interfacial Fenton-like reaction under visible light irradiation over etched CoxFeyO4–BiOBr photocatalysts. Issue 2 (20th December 2017) - Zhou, Ting; Xu, Yuanguo; Wang, Xiang; Huang, Shuquan; Xie, Meng; Xia, Jiexiang; Huang, Liying; Xu, Hui; Li, Huaming
Abstract : An in situ H2 O2 production and Fenton-like system, Co x Fe y O4 –BiOBr has been constructed. Co and Fe can build two redox cycles for ROSs (˙O2 − and ˙OH radicals) generation and the optimal composites were obtained. Abstract : In this study, we constructed an in situ Fenton-like photocatalytic system driven by visible-light irradiation. First, BiOBr, a benign in situ H2 O2 producer, was prepared via a simple hydrothermal method. Then, the accelerant (CoFe2 O4 nanoparticles as the precursor) for H2 O2 decomposition was loaded onto the surface of the BiOBr photocatalyst to build a well-contacted interface for reactive sites. Co x Fe y O4 nanoparticles etched to different extents were obtained by adjusting the solution pH (pH = 1, 3 and 7) during the composite preparation process. A group of green and efficient Co x Fe y O4 –BiOBr photocatalysts (abbreviated as CFB) (pH = 1, 3 and 7) were successfully synthesized. The optimal CFB material used for BPA photodegradation was 0.5% CFB (pH = 3). The reaction rate constant of 0.5% CFB (pH = 3) was 3.4 times higher than BiOBr (pH = 3). H2 O2 detection, ESR and radical trapping experiments demonstrated that much of the H2 O2 produced by BiOBr (pH = 3) was successfully decomposed to ˙O2 − and ˙OH, which played important roles with h + in the BPA photodegradation process, thereby a possible photocatalytic mechanism was proposed. Cycling experiments indicated the good stability of 0.5% CFB (pH = 3). This work may offer a green and efficient method for in situ H2 O2 generation and decomposition, thus, the secondary pollution and harsh conditions of the conventional Fenton reaction can be tactfully avoided.